From entry to elite: The relative age effect in the Australian football talent pathway - Tribolet, R.; Watsford, M. I.; Coutts, A. J.; Smith, C.; Fransen, J. (Journal of Science and Medicine in Sport, 2019)
Objectives: This study aimed to assess the first instance and prevalence of the Relative Age Effect (RAE) in the male Australian Football (AF) talent development pathway through to the Australian Football League (AFL).